AMERICAN SPEECH CULTURE: NORMS, PATTERNS, AND PRAGMATIC FEATURES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: This article explores the defining characteristics of American speech culture, examining how social values, cultural history, and regional diversity shape communication in the United States. American speech culture emphasizes informality, directness, and egalitarianism—features that often surprise or challenge speakers from more hierarchical societies. The article discusses key sociolinguistic norms such as turn-taking, small talk, silence interpretation, and assertiveness. It also highlights the impact of media, technology, and multiculturalism on evolving communication patterns in American English. Understanding these features is essential for effective intercultural communication and language instruction.